Preparation method of polyanion positive electrode material, positive electrode sheet and sodium ion battery

CN122977337APending Publication Date: 2026-10-27PETROCHINA SHENZHEN NEW ENERGY RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510524416.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,所使用的过渡金属都含有硝酸根等阴离子基团,这些基团在高温造粒、烧结过程中会严重腐蚀金属管道,降低设备使用寿命;且在高温烧结中,材料中的前驱体中的氮元素会生成一氧化氮、二氧化氮等气态氧化物的形式挥发,排放出污染气体,严重超过了本行业污染物排放限值;当烧结温度或者烧结时长不充分时,残留的氮元素会与有效离子熔融键合,影响相纯度与材料电化学性能

Benefits of technology

[0079]一、反硝化脱氮率高,本发明利用反硝化复合菌群,利用其酶促反应将前驱体浆料中的硝酸根阴离子逐步还原为N2,并控制浆料中N元素含量≤800ppm。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977337A_ABST
    Figure CN122977337A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a polyanion positive material, a positive plate and a sodium ion battery, and relates to the technical field of batteries, and comprises the following steps: S10, mixing a sodium ion source, an anion source, a transition metal nitrate, a carbon source, an organic solvent, water and a denitrifying bacteria agent, performing a denitrification reaction, and obtaining a precursor slurry; and S20, drying and sintering the precursor slurry to obtain the polyanion positive material. 2 In the liquid phase method, the nitrate anions existing in the solution are gradually degraded into N 2 by using the denitrifying bacteria agent, the residual amount of N elements in the solution is reduced, the pollution tail gas generated by high-temperature sintering of the material reaches the emission standard, and thus a high-energy-density positive material with a pure phase, excellent electrochemical performance and high powder compaction is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of batteries, and in particular to a method for preparing a polyanionic cathode material, a cathode sheet, and a sodium-ion battery. Background Technology

[0002] Polyanionic cathode materials are synthesized using a liquid-phase method, where each element can fully dissolve in aqueous solution. This allows for the orderly bonding of alkali metals, transition metals, and anionic chemical bonds, reducing intercrystalline porosity and resulting in polyanionic cathode materials with high phase purity and high powder compaction. However, the transition metals used contain anionic groups such as nitrate ions. These groups can severely corrode metal pipes during high-temperature granulation and sintering, reducing equipment lifespan. Furthermore, during high-temperature sintering, nitrogen in the precursors of the material volatilizes as gaseous oxides such as nitric oxide and nitrogen dioxide, releasing pollutants that significantly exceed the industry's emission limits. If the sintering temperature or duration is insufficient, residual nitrogen can fuse with effective ions, affecting phase purity and the material's electrochemical performance.

[0003] Therefore, by addressing the presence of anions such as nitrate in the liquid-phase method, and meeting the emission standards for exhaust gases during high-temperature sintering of materials, a high-energy-density cathode material with pure phase, excellent electrochemical performance, and high powder compaction can be obtained. Summary of the Invention

[0004] The main objective of this invention is to provide a method for preparing polyanionic cathode materials, cathode sheets, and sodium-ion batteries. The aim is to reduce the residual nitrogen element during the liquid-phase synthesis of polyanionic cathode materials, improve the phase purity and electrochemical performance of the polyanionic cathode materials, and also make them more environmentally friendly by avoiding the emission of polluting gases.

[0005] To achieve the above objectives, this invention proposes a method for preparing a polyanionic cathode material, characterized by comprising the following steps:

[0006] S10. Mix sodium ion source, anion source, transition metal nitrate salt, carbon source, organic solvent, water and denitrifying bacteria agent to carry out denitrification reaction to obtain precursor slurry;

[0007] S20. The precursor slurry is dried and sintered to obtain a polyanion cathode material.

[0008] In one embodiment, in step S10:

[0009] The denitrifying bacteria agent includes at least one of the following: an oxygen-inhibiting denitrifying bacteria agent, a facultative denitrifying bacteria agent, and an aerobic denitrifying bacteria agent.

[0010] In one embodiment, the denitrifying agent includes an anaerobic denitrifying agent, a facultative denitrifying agent, and an aerobic denitrifying agent, wherein the mass ratio of the anaerobic denitrifying agent, the facultative denitrifying agent, and the aerobic denitrifying agent is (0-8):(2-4):(0-6); and / or,

[0011] The oxygen-inhibiting denitrifying bacteria agent includes at least one of denitrifying lactobacillus and denitrifying Proteus; and / or,

[0012] The facultative denitrifying bacteria agent includes at least one of denitrifying Escherichia coli and denitrifying Staphylococcus aureus; and / or,

[0013] The aerobic denitrifying bacteria agent includes at least one of Pseudomonas, Alcaligenes, Paracoccus, and Bacillus.

[0014] In one embodiment, in step S10:

[0015] The temperature of the denitrification reaction is 0–50°C; and / or,

[0016] The denitrification reaction takes 1–48 hours; and / or,

[0017] The pH of the denitrification reaction is 4 to 10.

[0018] In one embodiment, in step S10:

[0019] The sodium ion source includes at least one selected from sodium nitrate, sodium formate, sodium acetate, sodium oxalate, sodium hydroxide, sodium citrate, and sodium carbonate; and / or,

[0020] The transition metal nitrate includes at least one of nickel nitrate, ferrous nitrate, manganese nitrate, cobalt nitrate, and titanium nitrate; and / or,

[0021] The anion source includes a phosphorus-containing compound, which includes at least one selected from hydrogen phosphate, pyrophosphate, phosphoric acid, pyrophosphate, and metaphosphoric acid; and / or,

[0022] The carbon source includes an organic water-soluble carbon source, which includes at least one selected from formic acid, acetic acid, tartaric acid, malic acid, oxalic acid, starch, glucose, citric acid, sucrose, lactose, maltose, and cyclodextrin; and / or,

[0023] The organic solvent includes alcohol-based organic solvents, which include at least one of methanol, ethanol, ethylene glycol, polyvinyl alcohol, polyethylene glycol, and polyacrylic acid.

[0024] In one embodiment, in step S10:

[0025] The mass ratio of the sodium ion source, the anion source, the transition metal nitrate salt, the carbon source, and the denitrifying bacteria is (12-14):(30-40):(40-45):(1-15):(0.01-1); and / or,

[0026] The nitrogen content in the precursor slurry is less than or equal to 800 ppm; and / or,

[0027] In the polyanionic cathode material, the concentration of the carbon source is 5-15%.

[0028] In one embodiment, step S20 includes: drying the precursor slurry to obtain precursor powder; and sintering the precursor powder to obtain a polyanion cathode material.

[0029] In one embodiment, in step S20:

[0030] The precursor slurry has a solid content of 45-60%; and / or,

[0031] The drying method includes at least one of freeze drying, fluidized bed drying, forced air drying, vacuum drying, spray drying, and flash drying; and / or,

[0032] The drying step includes: heating to 70-110°C at a heating rate of 2-5°C / min; and / or,

[0033] The sintering method includes sintering under an inert atmosphere, wherein the gas in the inert atmosphere includes at least one of nitrogen and argon; and / or,

[0034] The sintering temperature is 480–700°C; and / or,

[0035] The sintering time is 2 to 20 hours.

[0036] The present invention also proposes a positive electrode sheet, wherein the positive electrode sheet comprises a polyanion positive electrode material prepared by any of the above-described methods for preparing polyanion positive electrode materials.

[0037] The present invention also proposes a sodium-ion battery, which includes a negative electrode, an electrolyte, and a positive electrode as described above.

[0038] In the technical solution of this invention, nitrate anions present in the solution for preparing polyanionic cathode materials are gradually degraded into N by using denitrifying bacteria. 2This reduces the residual amount of nitrogen in the solution, ensuring that the polluting exhaust gas generated during high-temperature sintering of the material meets emission standards. At the same time, it prevents the residual nitrogen from melting and bonding with other ions, thereby improving the phase purity and electrochemical performance of the final polyanionic cathode material. This results in a high-energy-density cathode material with a pure phase, excellent electrochemical performance, and high powder compaction. Attached Figure Description

[0039] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0040] Figure 1 This is a scanning electron microscope image of the polyanionic cathode material (Na4Fe3(PO4)2P2O7 material) prepared in Example 1 of the present invention;

[0041] Figure 2 This is a scanning electron microscope image of the polyanionic cathode material (Na4Fe3(PO4)2P2O7 / C material) prepared in Comparative Example 1 of the present invention.

[0042] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0043] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0044] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indications will also change accordingly.

[0045] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution where both A and B are satisfied simultaneously. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.

[0046] Polyanionic cathode materials are synthesized using a liquid-phase method, where each element can fully dissolve in aqueous solution. This allows for the orderly bonding of alkali metals, transition metals, and anionic chemical bonds, reducing intercrystalline porosity and resulting in polyanionic cathode materials with high phase purity and high powder compaction. However, the transition metals used contain anionic groups such as nitrate ions. These groups can severely corrode metal pipes during high-temperature granulation and sintering, reducing equipment lifespan. Furthermore, during high-temperature sintering, the high-temperature pyrolysis temperature typically exceeds 600℃. At this temperature, elements such as sulfur and nitrogen in the precursors of the material will volatilize in the form of gaseous oxides such as sulfur dioxide, nitric oxide, and nitrogen dioxide, emitting polluting gases that severely exceed the industry's pollutant emission limits. If the sintering temperature or sintering time is insufficient, residual sulfur and nitrogen elements will moltenly bond with effective ions, affecting phase purity and the material's electrochemical performance.

[0047] In view of this, the present invention proposes a method for preparing a polyanionic cathode material, comprising the following steps:

[0048] Step S10: Mix sodium ion source, anion source, transition metal nitrate salt, carbon source, organic solvent, water and denitrifying bacteria agent to carry out denitrification reaction and obtain precursor slurry;

[0049] Step S20: Dry the precursor slurry and sinter it to obtain a polyanion cathode material.

[0050] This invention utilizes denitrifying bacteria to gradually degrade nitrate anions present in the solution used for preparing polyanionic cathode materials into N2. 2This reduces the residual amount of nitrogen in the solution, ensuring that the polluting exhaust gas generated during the high-temperature sintering of the material meets emission standards. At the same time, it prevents the residual nitrogen from molten bonding with elements such as Fe and P, thereby improving the phase purity and electrochemical performance of the final polyanionic cathode material. This results in a high-energy-density cathode material with a pure phase, excellent electrochemical performance, and high powder compaction.

[0051] It should be noted that denitrifying bacteria gradually reduce nitrate to nitrogen through a series of enzymatic reactions. 2 Its denitrification process mainly consists of four enzymatic reactions, each involving nitrate reductase (Nar), and its chemical reaction equation is: 2NO -3 +4H + +4e - =2NO -2 +2H₂O; Nitrite reductase (Nir), its chemical reaction equation is: 2NO -2 +4H + +2e - = 2NO + 2H₂O; Nitric oxide reductase (Nor), its chemical reaction equation is: 2NO + 2H⁺ + 2e⁻ - = N₂O + H₂O; Nitrous oxide reductase (N₂OR) reduces nitrate to N₂, and its chemical reaction equation is: N₂O + 2H₂O + +2e - =N 2 +H2O.

[0052] Furthermore, during step S20, it is also necessary to detect the exhaust gas during the sintering process, specifically the content of nitrogen oxides in the exhaust gas, specifically nitric oxide and nitrogen dioxide. The instruments used include one or more of the following: electrochemical detector, chemiluminescence detector, infrared absorption spectrometer, and laser-induced fluorescence spectrometer.

[0053] Furthermore, it should be noted that the emission limit for nitrogen oxides is ≤200mg / m3. In Table 4 of the "Emission Standard of Pollutants for Inorganic Chemical Industry" (GB 31573-2015), the emission limit for nitrogen oxides is 200mg / m3.

[0054] In some embodiments, in step S10: the denitrifying agent includes at least one of the following: an oxygen-inhibiting denitrifying agent, a facultative denitrifying agent, and an aerobic denitrifying agent. Specifically, the denitrifying agent can be any one of these denitrifying bacteria, or a mixture of any two or three denitrifying bacteria, as long as it can reduce the residual amount of nitrogen in the solution, so that the subsequent combustion tail gas meets the emission standards and improves phase purity and electrochemical performance.

[0055] Furthermore, the denitrifying bacteria agent includes an anaerobic denitrifying bacteria agent, a facultative denitrifying bacteria agent, and an aerobic denitrifying bacteria agent, with a mass ratio of (0-8):(2-4):(0-6) for the anaerobic denitrifying bacteria agent, the facultative denitrifying bacteria agent, and the aerobic denitrifying bacteria agent. A reasonable ratio within this range can fully leverage the advantages of each agent and improve the overall denitrification efficiency. For example, in some cases, the anaerobic denitrifying bacteria initiate the initial reaction first, and then the facultative denitrifying bacteria continue to complete the remaining process, thereby achieving more thorough nitrogen removal.

[0056] In some embodiments, the oxygen-suppressing denitrifying bacterial agent includes at least one of denitrifying lactobacillus and denitrifying Proteus; these agents mainly refer to microorganisms active under anaerobic conditions (i.e., in environments with almost no dissolved oxygen). They are able to use nitrate as an electron acceptor for respiration, gradually reducing nitrate to nitrite, nitrous oxide, and nitric oxide, ultimately generating nitrogen gas.

[0057] In some embodiments, the facultative denitrifying bacteria include at least one of denitrifying Escherichia coli and denitrifying Staphylococcus aureus; the facultative denitrifying bacteria are capable of growing and performing denitrification under both aerobic and anaerobic conditions. When oxygen is present in the environment, these bacteria preferentially use oxygen as an electron acceptor; under hypoxic or anaerobic conditions, they will switch to using nitrates or other oxidized nitrogen compounds as electron acceptors for denitrification.

[0058] In some embodiments, the aerobic denitrifying agent includes at least one of Pseudomonas, Alcaligenes, Paracoccus, and Bacillus. The aerobic denitrifying agent can also perform denitrification in an aerobic environment and can reduce nitrates in the presence of oxygen. Its mechanism of action may include using other organic matter as electron donors to directly convert nitrates into nitrogen in the presence of oxygen.

[0059] In some embodiments, in step S10: the temperature of the denitrification reaction is 0–50°C; the time of the denitrification reaction is 1–48 h; the pH of the denitrification reaction is 4–10, and the denitrifying bacteria can maintain a certain level of activity within a wide temperature range. These conditions are selected to ensure that the denitrification reaction can be carried out effectively under various environmental conditions and to adapt to different application scenarios.

[0060] In some embodiments, in step S10: the sodium ion source includes at least one of sodium nitrate, sodium formate, sodium acetate, sodium oxalate, sodium hydroxide, sodium citrate, and sodium carbonate; these compounds provide sodium ions (Na+). +Sodium hydroxide (SO4) is a fundamental component of the cathode material in sodium-ion batteries. The choice of different sodium ion sources depends primarily on their solubility, reactivity, and impact on the structure and performance of the final product. For example, sodium hydroxide can be used to adjust the pH of the solution, affecting the nucleation and crystal growth process; while using organic sodium salts such as sodium citrate or sodium acetate may help improve the uniformity and dispersibility of the material.

[0061] The nitrate transition metal salts include at least one of nickel nitrate, ferrous nitrate, manganese nitrate, cobalt nitrate, and titanium nitrate; these transition metal salts provide the necessary transition metal ions (Ni... 2+ ,Fe 2+ / Fe 3+ ,Mn 2+ Co 2+ Ti 4+ These are electrochemically active centers that participate in redox reactions during charge and discharge. The selection of different transition metals and their proportions can directly affect key performance indicators of materials, such as energy density, power density, and cycle life. Furthermore, nitrate compounds typically have good water solubility, which is beneficial for uniform mixing and subsequent chemical reactions.

[0062] Furthermore, specifically, when ferrous nitrate is added as a transition metal, iron can typically switch between two oxidation states, +2 and +3, which is the basis for its participation in electrochemical reactions as an active material. Therefore, it is not necessary to use additional oxidants or reductants like ammonium metavanadate to adjust its valence state. However, when titanium nitrate is used, titanium can exhibit multiple oxidation states, such as +2, +3, and +4, in different compounds. In most high-performance sodium-ion battery cathode materials, it is necessary to add appropriate oxidants or reductants to adjust its valence state. Ammonium metavanadate can be used as an oxidant to ensure that titanium reaches the target titanium oxide state; typically, ammonium metavanadate is chosen as the reductant.

[0063] The anion source includes phosphorus-containing compounds, which include at least one of hydrogen phosphate, pyrophosphate, phosphoric acid, pyrophosphate, and metaphosphoric acid. These compounds are used to construct polyanionic frameworks, such as sodium iron phosphate, which are crucial for improving the structural stability and electrochemical performance of materials. Phosphorus-containing compounds not only provide the anionic framework but also enable the tuning of the material's lattice parameters and electronic conductivity.

[0064] The carbon source includes an organic water-soluble carbon source, comprising at least one of formic acid, acetic acid, tartaric acid, malic acid, oxalic acid, starch, glucose, citric acid, sucrose, lactose, maltose, and cyclodextrin. It is primarily used as a reducing agent or carbon source to form a conductive carbon network during high-temperature calcination, thereby improving the overall conductivity of the material. Furthermore, some carbon sources can also act as complexing agents to help control the distribution of metal ions in the precursor solution, thus optimizing the morphology and particle size of the final product.

[0065] The organic solvents include alcohol-based organic solvents, specifically at least one selected from methanol, ethanol, ethylene glycol, polyvinyl alcohol, polyethylene glycol, and polyacrylic acid. Water is one of the most commonly used solvents due to its environmental friendliness and low cost. Alcohol-based organic solvents can improve the solubility of certain poorly soluble substances and help control the crystallization process of materials. High molecular weight alcohol solvents such as polyvinyl alcohol and polyethylene glycol can also form a protective film on the material surface, preventing particle aggregation and improving dispersibility.

[0066] In some embodiments, in step S10:

[0067] The mass ratio of the sodium ion source, the anion source, the transition metal nitrate salt, the carbon source, and the denitrifying bacteria is (12-14):(30-40):(40-45):(1-15):(0.01-1). Within this range, materials are not wasted, the chemical reaction pathway in the synthesis process is optimized, and the electrochemical performance of the prepared polyanion cathode material is significantly improved.

[0068] In some embodiments, the nitrogen content in the precursor slurry is less than or equal to 800 ppm. In the preparation process of sodium batteries, the lower the nitrogen content, the better. Excessive nitrogen can also generate unpredictable byproducts, affecting the purity of the final cathode material. In the embodiments of the present invention, a nitrogen content of less than or equal to 800 ppm is chosen to balance cost and ensure the electrochemical performance of the material.

[0069] In polyanionic cathode materials, the concentration of the carbon source ranges from 5% to 15%. Since the type and concentration of the carbon source have a significant impact on the denitrification reaction, excessively high or low carbon content will affect the electronic conductivity of the material, thereby affecting battery performance. In the embodiments of the present invention, the concentration of the carbon source is preferably 13%, which helps to form a uniform carbon coating layer, improves the contact between particles, and enhances the cycle stability and rate performance of the material.

[0070] In some embodiments, step S20 includes: drying the precursor slurry to obtain precursor powder; and sintering the precursor powder to obtain a polyanion cathode material.

[0071] Furthermore, in step S20: the solid content of the precursor slurry is 45% to 60%, specifically, it can be 45%, 50% or 60%. Within this range, not only can the drying and sintering process be optimized, but the physicochemical properties and electrochemical performance of the final polyanion cathode material can also be significantly improved.

[0072] In some embodiments, the drying method includes at least one of freeze drying, fluidized bed drying, forced air drying, vacuum drying, spray drying, and flash drying. Different drying methods are adapted to different scales of production needs, ensuring efficient and uniform removal of moisture.

[0073] In some embodiments, the drying step includes: heating to 70-110°C at a heating rate of 2-5°C / min; specifically, the drying temperature can be 70°C, 75°C, 80°C, or 110°C, etc. The drying process of the present invention is a low-temperature, low-heating-rate drying crystallization method, controlling the temperature between 70-110°C to ultimately achieve solid-liquid separation, avoiding excessively rapid heating rates that would cause the moisture to disappear instantly, forming a hollow structure and affecting the compaction density of the material.

[0074] In some embodiments, the sintering method includes sintering under an inert atmosphere, wherein the gas in the inert atmosphere includes at least one of nitrogen and argon; an inert atmosphere helps maintain the original composition of the material and prevents the material from being oxidized at high temperatures, especially in systems containing transition metals, where oxygen may cause the formation of undesirable oxides that affect the electrochemical performance of the material.

[0075] In some embodiments, the sintering temperature is 480–700°C, and the sintering time is 2–20 h. Specifically, the sintering temperature can be 480°C, 500°C, 580°C, or 700°C, and the sintering time can be 2 h, 10 h, 15 h, or 20 h. Within this range, appropriate sintering temperature and sintering time help to form a uniform carbon network, improve the overall conductivity of the material, and enhance mechanical strength and thermal stability.

[0076] The present invention also proposes a positive electrode sheet, wherein the positive electrode sheet comprises a polyanion positive electrode material prepared by any of the above-described methods for preparing polyanion positive electrode materials.

[0077] The present invention also proposes a sodium-ion battery, which includes a negative electrode, an electrolyte, and a positive electrode as described above.

[0078] In summary, the technical solution of the present invention has the following beneficial effects:

[0079] I. High denitrification rate: This invention utilizes a denitrifying complex microbial community, which uses its enzymatic reaction to gradually reduce nitrate anions in the precursor slurry to nitrogen.2 And control the nitrogen content in the slurry to ≤800ppm.

[0080] Second, the compaction density is high. The present invention uses a low-temperature, low-heating-rate drying crystallization method to dry the precursor slurry obtained by the liquid phase method. The evaporation temperature is controlled between 70 and 110°C, and solid-liquid separation is finally achieved. This avoids the problem of excessively fast heating rate, which would cause the water to disappear instantly and form a hollow structure, thus affecting the compaction density of the material.

[0081] Third, it has excellent electrochemical performance. The reduction of nitrogen in the material allows for the full melting and bonding of effective ions, which greatly improves the phase purity of the polyanion cathode material after sintering, thus fully releasing the electrochemical performance of the material.

[0082] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0083] Example 1

[0084] Step 1: The preparation of the polyanion cathode material is as follows:

[0085] 1) Weigh water-soluble ferrous nitrate, phosphoric acid, and sodium hydroxide in a stoichiometric ratio of 3:4:4, specifically 539.55g / 391.88g / 159.96g respectively. Dissolve them in water to form a light green ionic solution. Add glucose, polyethylene glycol 400, denitrifying lactic acid bacteria, and denitrifying staphylococci to the light green ionic solution and mix to carry out the denitrification reaction to obtain the precursor slurry. The denitrification temperature is 30℃; the denitrification time is 40h; the pH is controlled at 7-8; and the nitrogen content of the precursor slurry is 120ppm.

[0086] 2) The precursor slurry is dried to obtain a light yellow precursor powder. 200g of the light yellow precursor powder is taken. It should be noted that glucose accounts for 8% of the precursor powder weight; polyethylene glycol accounts for 5% of the precursor powder weight; denitrifying lactic acid bacteria and denitrifying staphylococci are prepared in a 4:1 ratio, accounting for 0.8% of the precursor powder weight; ferrous nitrate accounts for 42.7% of the precursor powder weight; phosphoric acid accounts for 30.9% of the precursor powder weight; and sodium hydroxide accounts for 12.6% of the precursor powder weight. The solid content is controlled at 60%. After stirring evenly, the precursor slurry of step 1) above is formed.

[0087] 3) The precursor powder is sintered at 600℃ for 15 hours and then cooled naturally to obtain Na4Fe3(PO4)2P2O7 / C material, which is also a polyanion cathode material.

[0088] Step 2, the preparation of the sodium-ion battery is as follows:

[0089] The Na4Fe3(PO4)2P2O7 / C, acetylene black, and polyvinylidene fluoride (PVDF) binder prepared in step 1 were mixed in a mass ratio of 8:1:1 to form a slurry. The slurry was then uniformly coated onto aluminum foil using a 140µm four-sided coating tool. The membrane was then dried in a vacuum drying oven at 110°C for 5 hours. The electrode membrane was punched into a 0.5mm radius disc using a punching machine. The counter electrode was made of metallic sodium, the electrolyte was commercially available sodium-ion battery electrolyte, and the separator was a PP / PE / PP three-layer separator. The membrane was then assembled into a CR2016 button cell in an Ar gas glove box.

[0090] Example 2

[0091] Step 1: The preparation of the polyanion cathode material is as follows:

[0092] 1) Water-soluble titanium nitrate, ammonium metavanadate, phosphoric acid, and sodium hydroxide were weighed according to the stoichiometric ratio of the molecular formula 1:1:3:3, with specific mass measurements of 295.87g / 116.94g / 293.91g / 119.97g respectively. Water was added to dissolve them, forming a light grayish-white ionic solution. Sucrose, ethylene glycol, denitrifying Proteus bacteria, and denitrifying Escherichia coli were added to the solution and mixed to carry out a denitrification reaction, yielding a precursor slurry. The denitrification temperature was 35℃; the denitrification time was 35h; the pH was controlled at 6-7; and the nitrogen content of the precursor slurry was measured to be 125ppm.

[0093] 2) Slowly evaporate the above precursor slurry to obtain a light gray precursor powder. Take 200g of the light gray precursor powder; sucrose accounts for 9% of the precursor powder weight; ethylene glycol accounts for 4% of the precursor powder weight; denitrifying Proteus and denitrifying Escherichia coli are prepared in a 7:3 ratio, accounting for 1.0% of the precursor powder weight; titanium nitrate accounts for 30.8% of the precursor powder weight; ammonium metavanadate accounts for 12.1% of the precursor powder weight; phosphoric acid accounts for 30.6% of the precursor powder weight; sodium hydroxide accounts for 12.5% ​​of the precursor powder weight. Control the solid content at 55%, stir evenly, and form the precursor slurry of step 1) above.

[0094] 3) The precursor powder was kept at 650℃ for 17h and then allowed to cool naturally to obtain Na3TiV(PO4)3 / C material;

[0095] Step 2, the preparation of the sodium-ion battery is as follows:

[0096] The Na3TiV(PO4)3 / C, acetylene black, and polyvinylidene fluoride (PVDF) binder prepared in step 1 were mixed into a slurry at a mass ratio of 8:1:1. The black slurry was then coated onto aluminum foil using a 140µm four-sided coating apparatus. The membrane was then dried under vacuum at 115°C for 15 hours. The electrode membrane was punched into a 0.5mm radius disc using a die-cutting machine. The counter electrode was made of metallic sodium, the electrolyte was a commercially available sodium-ion battery electrolyte, and the separator was a PP / PE / PP three-layer separator. The CR2016 button cell was assembled in an Ar gas glove box.

[0097] Example 3

[0098] Step 1: The preparation of the polyanion cathode material is as follows:

[0099] 1) Water-soluble manganese nitrate, ammonium metavanadate, phosphoric acid, and sodium hydroxide were weighed in a stoichiometric ratio of 1:1:3:3, with specific mass values ​​of 178.94g / 116.94g / 293.91g / 119.97g respectively. Water was added to dissolve them, forming a light grayish-white ionic solution. Starch, polyvinyl alcohol, Staphylococcus denitrifyingis, and Pseudomonas spp. were then added to the solution and mixed to carry out a denitrification reaction, yielding a precursor slurry. The denitrification temperature was 25℃, the denitrification time was 24h, the pH was controlled at 6-7, and the nitrogen content of the precursor slurry was 340ppm.

[0100] 2) Slowly evaporate the above precursor slurry to obtain a light gray precursor powder. Take 200g of the light gray precursor powder, wherein the amounts of each component added in step 1) are as follows: starch accounts for 7% of the precursor powder weight; polyvinyl alcohol accounts for 9% of the precursor powder weight; Staphylococcus denitrifyingis and Pseudomonas spp. are prepared in a 2:3 ratio, accounting for 1.0% of the precursor powder weight; manganese nitrate accounts for 20.9% of the precursor powder weight; ammonium metavanadate accounts for 13.7% of the precursor powder weight; phosphoric acid accounts for 34.4% of the precursor powder weight; and sodium hydroxide accounts for 14% of the precursor powder weight. The solid content is controlled at 45%, and after stirring evenly, a viscous slurry is formed.

[0101] 3) The precursor powder was kept at 700℃ for 20h and then allowed to cool naturally to obtain Na3MnV(PO4)3 / C material;

[0102] Step 2, the preparation of the sodium-ion battery is as follows:

[0103] The Na3MnV(PO4)3 / C, acetylene black, and polyvinylidene fluoride (PVDF) binder prepared in step 1 were mixed in a mass ratio of 8:1:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 140µm four-sided coating apparatus. The membrane was then dried under vacuum at 120°C for 5 hours. The electrode membrane was punched into a 0.5mm radius disc using a punching machine. The counter electrode was made of metallic sodium, the electrolyte was a commercially available sodium-ion battery electrolyte, and the separator was a PP / PE / PP three-layer separator. The CR2016 button cell was assembled in an Ar gas glove box.

[0104] Example 4

[0105] The difference between Example 1 and Example 4 is that Example 4 uses only a single denitrifying lactobacillus, accounting for 0.8% of the precursor powder weight, and the nitrogen content of the precursor slurry is 302 ppm. The rest are similar.

[0106] Example 5

[0107] The difference from Example 1 is that the Example uses a mixture of denitrifying lactobacillus, denitrifying staphylococcus, and pseudomonas in a 1:1:3 ratio, accounting for 0.8% of the precursor powder weight, and the nitrogen content of the precursor slurry was measured to be 269 ppm. The rest are similar.

[0108] Comparative Example 1

[0109] Step 1: The preparation of the polyanion cathode material is as follows:

[0110] 1) Weigh water-soluble ferrous nitrate, phosphoric acid, and sodium hydroxide in a stoichiometric ratio of 3:4:4, with masses of 539.55g / 391.88g / 159.96g respectively. Dissolve them in water to form a light green ionic solution. Add glucose and polyethylene glycol 400 to the light green ionic solution and mix. Stir until homogeneous to obtain the precursor slurry. Control the solid content of the precursor slurry to 60% and the pH of the precursor slurry to 7-8. The nitrogen content of the precursor slurry is detected to be 7800ppm.

[0111] 2) The precursor slurry is dried to obtain 200g of light yellow precursor powder, wherein the amounts of each component added in step 1) are as follows: glucose accounts for 8% of the weight of the precursor powder; polyethylene glycol accounts for 5% of the weight of the precursor powder; ferrous nitrate accounts for 42.7% of the weight of the precursor powder; phosphoric acid accounts for 30.9% of the weight of the precursor powder; and sodium hydroxide accounts for 12.6% of the weight of the precursor powder.

[0112] 3) The precursor powder is sintered at 600℃ for 15 hours and then cooled naturally to obtain Na4Fe3(PO4)2P2O7 / C material, which is also a polyanion cathode material.

[0113] Step 2, the preparation of the sodium-ion battery is as follows:

[0114] The Na4Fe3(PO4)2P2O7 / C, acetylene black, and polyvinylidene fluoride (PVDF) binder prepared in step 1 were mixed in a mass ratio of 8:1:1 to form a slurry. The slurry was then uniformly coated onto aluminum foil using a 140µm four-sided coating tool. The membrane was then dried in a vacuum drying oven at 110°C for 5 hours. The electrode membrane was punched into a 0.5mm radius disc using a punching machine. The counter electrode was made of metallic sodium, the electrolyte was a commercially available sodium-ion battery electrolyte, and the separator was a PP / PE / PP three-layer separator. The membrane was then assembled into a CR2016 type button cell in an Ar gas glove box.

[0115] Comparative Example 2

[0116] Step 1: The preparation of the polyanion cathode material is as follows:

[0117] 1) Weigh water-soluble titanium nitrate, ammonium metavanadate, phosphoric acid, and sodium hydroxide in a stoichiometric ratio of 1:1:3:3, with masses of 295.87g / 116.94g / 293.91g / 119.97g respectively. Dissolve them in water to form a light grayish-white ionic solution. Add sucrose and ethylene glycol to the light grayish-white ionic solution and stir until homogeneous to obtain the precursor slurry. Control the solid content of the precursor slurry to 55%, control the pH of the precursor slurry to 7-8, and test the nitrogen content of the precursor slurry to be 6500ppm.

[0118] 2) The above precursor slurry was slowly evaporated to dryness to obtain 200g of light gray precursor powder; wherein, the amounts of each component added in step 1) were as follows: sucrose accounted for 9% of the weight of the precursor powder; ethylene glycol accounted for 4% of the weight of the precursor powder; titanium nitrate accounted for 30.8% of the weight of the precursor powder; ammonium metavanadate accounted for 12.1% of the weight of the precursor powder; phosphoric acid accounted for 30.6% of the weight of the precursor powder; and sodium hydroxide accounted for 12.5% ​​of the weight of the precursor powder.

[0119] 3) The precursor powder was kept at 650℃ for 17h and then allowed to cool naturally to obtain Na3TiV(PO4)3 / C material;

[0120] Step 2, the preparation of the sodium-ion battery is as follows:

[0121] Na3TiV(PO4)3 / C, acetylene black, and polyvinylidene fluoride (PVDF) binder were mixed in a mass ratio of 8:1:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 140µm four-sided coating apparatus. The membrane was then dried under vacuum at 115°C for 15 hours. The electrode membrane was punched into a 0.5mm radius disc using a die-cutting machine. Metallic sodium was used as the counter electrode, and commercially available sodium-ion battery electrolyte was used. A PP / PE / PP three-layer separator was used. The membrane was then assembled into a CR2016 button cell in an Ar gas glove box.

[0122] Comparative Example 3

[0123] Step 1: The preparation of the polyanion cathode material is as follows:

[0124] 1) Weigh water-soluble manganese nitrate, ammonium metavanadate, phosphoric acid, and sodium hydroxide according to the stoichiometric ratio of the molecular formula 1:1:3:3, add water to mix and dissolve to form a light grayish-white ionic solution, add starch and polyvinyl alcohol to the light grayish-white ionic solution and stir evenly to obtain the precursor slurry; control the solid content of the precursor slurry at 45%, control the pH of the precursor slurry at 6-7, and detect the nitrogen content of the precursor slurry at 7044 ppm;

[0125] 2) The above precursor slurry was slowly evaporated to obtain 200g of light gray precursor powder, wherein starch accounted for 7% of the precursor powder by weight; polyvinyl alcohol accounted for 9% of the precursor powder by weight; manganese nitrate accounted for 20.9% of the precursor powder by weight; ammonium metavanadate accounted for 13.7% of the precursor powder by weight; phosphoric acid accounted for 34.4% of the precursor powder by weight; and sodium hydroxide accounted for 14% of the precursor powder by weight.

[0126] 3) The precursor powder was kept at 700℃ for 20h and then allowed to cool naturally to obtain Na3MnV(PO4)3 / C material;

[0127] Step 2, the preparation of the sodium-ion battery is as follows:

[0128] The Na3MnV(PO4)3 / C, acetylene black, and polyvinylidene fluoride (PVDF) binder prepared in step 1 were mixed into a slurry at a mass ratio of 8:1:1. The black slurry was then coated onto aluminum foil using a 140µm four-sided coating apparatus. The membrane was then dried under vacuum at 120°C for 5 hours. The electrode membrane was punched into a 0.5mm radius disc using a die-cutting machine. The counter electrode was made of metallic sodium, the electrolyte was a commercially available sodium-ion battery electrolyte, and the separator was a PP / PE / PP three-layer separator. The membrane was then assembled into a CR2016 type button cell in an Ar gas glove box.

[0129] Performance testing

[0130] Nitrogen oxide emission test

[0131] The amount of nitrogen oxide emissions during step 1 of the preparation process of the polyanionic cathode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was detected using a chemiluminescence detector. The results are shown in Table 1.

[0132] Table 1

[0133]

[0134] Electrochemical testing

[0135] Constant current charge-discharge tests were conducted on the coin cells prepared in Examples 1-3 and Comparative Examples 1-3. The test results are shown in Table 2. Simultaneously, the powder compaction density (g / cm³) at 300 MPa was measured. 3 The test results are shown in Table 3.

[0136] Table 2 Comparison of discharge capacity between embodiments of the present invention and comparative examples.

[0137]

[0138] Table 3 Comparison of physical parameters between embodiments of the present invention and comparative examples.

[0139]

[0140] The specific explanations based on Tables 2 and 3 are as follows:

[0141] (1) The coin cell prepared in Example 1 was subjected to constant current charge-discharge testing at a current density of 0.1C (1C = 129 mAh / g). The electrode exhibited a reversible specific capacity of 113 mAh / g and an average discharge potential of 3.05 V, demonstrating high capacity utilization. Compared with Comparative Example 1 (93 mAh / g), this electrode has a higher reversible capacity, indicating that the material has less residual nitrogen, higher phase purity after sintering, and higher reversible insertion / extraction capacity. Figure 1 The image shows a SEM image of the Na4Fe3(PO4)2P2O7 material from Example 1. The material consists of square particles approximately 2-3 μm in size, with a relatively dense particle distribution, no microporous structure, and low interfacial side reactions. The material prepared in Example 1 was measured using a powder compaction density tester under a test condition of 300 MPa, yielding a compaction density of 2.21 g / cm³. 3 .

[0142] (2) A constant current charge-discharge test was conducted on the coin cell in Example 2, and the results showed that the current density was 0.1C (1C = 120 mAh / g). The reversible specific capacity of the electrode was 114 mAh / g, corresponding to a capacity utilization rate of 95%. Using a powder compaction density tester, the compaction density of the Na3TiV(PO4)3 / C material in Example 2 was measured at 300 MPa, which was 2.15 g / cm, about 15.2% higher than that of Comparative Example 2. This indicates that the material prepared by this process has a dense crystal distribution, larger grain size, and more compact interparticles. The amount of Ti ions dissolved from the material surface is reduced, and the structural stability is improved.

[0143] (3) Constant current charge-discharge tests were conducted on the coin cell of Example 3. The test results showed a current density of 0.1C (1C = 119 mAh / g), a reversible specific capacity of 110 mAh / g, and a capacity utilization rate as high as 92.4%. The improved phase purity of the material allowed for the full release of its capacity. The material prepared in Example 3 was measured using a powder compaction density tester under a test condition of 300 MPa. The measured compaction density was 2.09 g / cm³, which is about 17.1% higher than that of Comparative Example 3, indicating that the material prepared by this process has a dense crystal distribution.

[0144] (4) A constant current charge-discharge test was conducted on the coin cell of Comparative Example 1, and the test result showed a current density of 0.1C (1C = 129 mAh / g). The reversible specific capacity of this electrode was 93 mAh / g, indicating that the material contains impurity phases such as Na3FePO4 and Na2FeP2O7, as well as interfacial reactions with N elements, which cause the electrochemical performance of the material to degrade; and Figure 2 The image shows a SEM image of the Na4Fe3(PO4)2P2O7 / C material from Comparative Example 1. It consists of spherical particles approximately 3–4 μm in size, with numerous voids between the crystals. The compacted density of the material from Comparative Example 1 was measured using a powder compaction density tester under a test condition of 300 MPa, yielding a compaction density of 1.87 g / cm³. 3 The material has low compaction.

[0145] (5) A constant current charge-discharge test was conducted on the coin cell of Comparative Example 2, and the test result showed a current density of 0.1C (1C = 129 mAh / g). The reversible specific capacity of this electrode was 87 mAh / g, while the compaction density of the Na3TiV(PO4)3 / C material in Comparative Example 2 was only 1.78 g / cm³. 3 The electrochemical performance of this material is lower than that of Example 2. This is because the material synthesized by this process has high porosity, low crystallinity, and a high degree of side reactions between residual nitrogen elements at the interface and the electrolyte during the sodium insertion / extraction process.

[0146] (6) A constant current charge-discharge test was conducted on the coin cell of Comparative Example 3, and the test result showed a current density of 0.1C (1C = 120 mAh / g). The reversible specific capacity of this electrode was 89 mAh / g, corresponding to a capacity utilization rate of 74.2%. The material prepared in Comparative Example 3 was measured using a powder compaction density tester under a test condition of 300 MPa, and the compaction density was found to be 1.94 g / cm³. 3 This indicates that the material has low phase purity and contains many gaps, which increases the contact area with the electrolyte. As a result, during the sodium insertion / extraction process, the manganese ions at the interface dissolve into the electrolyte due to the Ginger-Taylor effect, leading to poor electrochemical performance.

[0147] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.

Claims

1. A method for preparing a polyanionic cathode material, characterized in that, Includes the following steps: S10. Mix sodium ion source, anion source, transition metal nitrate salt, carbon source, organic solvent, water and denitrifying bacteria agent to carry out denitrification reaction to obtain precursor slurry; S20. The precursor slurry is dried and sintered to obtain a polyanion cathode material.

2. The method for preparing the polyanionic cathode material as described in claim 1, characterized in that, In step S10: The denitrifying bacteria agent includes at least one of the following: an oxygen-inhibiting denitrifying bacteria agent, a facultative denitrifying bacteria agent, and an aerobic denitrifying bacteria agent.

3. The method for preparing the polyanionic cathode material as described in claim 2, characterized in that, The denitrifying bacteria agent includes an anaerobic denitrifying bacteria agent, a facultative denitrifying bacteria agent, and an aerobic denitrifying bacteria agent, wherein the mass ratio of the anaerobic denitrifying bacteria agent, the facultative denitrifying bacteria agent, and the aerobic denitrifying bacteria agent is (0-8):(2-4):(0-6); and / or, The oxygen-inhibiting denitrifying bacteria agent includes at least one of denitrifying lactobacillus and denitrifying Proteus; and / or, The facultative denitrifying bacteria agent includes at least one of denitrifying Escherichia coli and denitrifying Staphylococcus aureus; and / or, The aerobic denitrifying bacteria agent includes at least one of Pseudomonas, Alcaligenes, Paracoccus, and Bacillus.

4. The method for preparing the polyanionic cathode material as described in claim 1, characterized in that, In step S10: The denitrification reaction is carried out at a temperature of 25–50°C; and / or, The denitrification reaction takes 1–48 hours; and / or, The pH of the denitrification reaction is 4 to 10.

5. The method for preparing the polyanionic cathode material as described in claim 1, characterized in that, In step S10: The sodium ion source includes at least one selected from sodium nitrate, sodium formate, sodium acetate, sodium oxalate, sodium hydroxide, sodium citrate, and sodium carbonate; and / or, The transition metal nitrate includes at least one of nickel nitrate, ferrous nitrate, manganese nitrate, cobalt nitrate, and titanium nitrate; and / or, The anion source includes a phosphorus-containing compound, which includes at least one selected from hydrogen phosphate, pyrophosphate, phosphoric acid, pyrophosphate, and metaphosphoric acid; and / or, The carbon source includes an organic water-soluble carbon source, which includes at least one selected from formic acid, acetic acid, tartaric acid, malic acid, oxalic acid, starch, glucose, citric acid, sucrose, lactose, maltose, and cyclodextrin; and / or, The organic solvent includes alcohol-based organic solvents, which include at least one of methanol, ethanol, ethylene glycol, polyvinyl alcohol, polyethylene glycol, and polyacrylic acid.

6. The method for preparing the polyanionic cathode material as described in claim 1, characterized in that, In step S10: The mass ratio of the sodium ion source, the anion source, the transition metal nitrate salt, the carbon source, and the denitrifying bacteria is (12-14):(30-40):(40-45):(1-15):(0.01-1); and / or, The nitrogen content in the precursor slurry is less than or equal to 800 ppm; and / or, In the polyanionic cathode material, the concentration of the carbon source is 5-15%.

7. The method for preparing the polyanionic cathode material as described in claim 1, characterized in that, Step S20 includes: drying the precursor slurry to obtain precursor powder; sintering the precursor powder to obtain polyanion cathode material.

8. The method for preparing the polyanionic cathode material as described in claim 7, characterized in that, In step S20: The precursor slurry has a solid content of 45-60%; and / or, The drying method includes at least one of freeze drying, fluidized bed drying, forced air drying, vacuum drying, spray drying, and flash drying; and / or, The drying step includes: heating to 70-110°C at a heating rate of 2-5°C / min; and / or, The sintering method includes sintering under an inert atmosphere, wherein the gas in the inert atmosphere includes at least one of nitrogen and argon; and / or, The sintering temperature is 480–700°C; and / or, The sintering time is 2 to 20 hours.

9. A positive electrode plate, characterized in that, The positive electrode sheet includes the polyanion positive electrode material prepared by the method for preparing polyanion positive electrode material as described in any one of claims 1 to 8.

10. A sodium-ion battery, characterized in that, The sodium-ion battery includes a negative electrode, an electrolyte, and a positive electrode as described in claim 9.